Camille Pissarro - Venezia, Mike. (New York Children's Press, 2003)
Describes the life and work of the nineteenth-century French painter Camille Pissarro.
1 - 6
Keywords: Pissarro, Camille, 1830-1903.; Artists; Painting, French; Getting to know the world's greatest artists